The Role Of Resource Readiness In Team Interaction Through The Mediating Role Of Innovation Talent Capability - Israa Abdulhasan Oleiwi (Journal of Advances in Accounting, Economics, and Management, 2025)
The research aims to measure the role of Resource Readiness, represented by (Cognitive Readiness, Affective Readiness, Intentional Readiness), in Team Interaction, represented by (Supportive Interaction, Compulsive Interaction), through the mediating role of Innovation Talent Capability, represented by (Knowledge, Training and Development), in a sample of faculty members at the Polytechnic College - Al-Qadisiyah. This objective was set to address the posed problem, which is a conceptual question: (Is there a role for Resource Readiness in Team Interaction through the mediating role of Innovation Talent Capability among the faculty members at Al-Qadisiyah Polytechnic College?) To determine the level of the research variables, the descriptive analytical approach was adopted using a questionnaire. A total of 125 questionnaires were distributed, of which 107 were retrieved, with 102 deemed valid for analysis and 5 forms damaged. This indicates a response rate of 81.6%. Therefore, the study relied on SPSS & AMOS software to analyse the data and assess the levels of its variables. The results showed that Human Resource Readiness, in terms of Cognitive Readiness, Affective Readiness, and Intentional Readiness, is positively associated with Team Interaction and Innovation Talent Capability (including Knowledge, and Training and Development). The study also revealed that Resource Readiness has high significance and mechanisms in improving Team Interaction through the mediating role of Innovation Talent Capability, contributing to the formation of positive relationships among colleagues to ensure the college's ability to enhance its internal capabilities. The study recommended that the college should focus on establishing new departments and faculties that keep pace with development and provide new methods and ideas that serve the labour market and improve both internal and external work contexts, as these represent an important pillar in producing specialists with high creative talent.